DISTRIBUTION DYNAMICS OF ZOOPLANKTON IN TYULENIY ISLAND WATERS OF THE CASPIAN SEA - Magomed M. Osmanov; Nukhkadi I. Rabazanov; Ruslan M. Barkhalov; Fangiz Sh. Amaeva; Murad M. Aligadzhiev; Aishat A. Abdurakhmanova (Юг России: экология, развитие, 2019)
Aim. It is not possible to study the mechanisms of formation and functioning of the Caspian coastal ecosystems without analyzing the hydrobiological situation of the surrounding water area as a whole. In this regard, the main objective of the research is to study the biodiversity and the quantitative assessment of the zooplankton communities of the coastal waters of Tyuleniy Island and its lagoon areas. Methods. Zooplankton samples were selected seasonally using quantitative methods in order to assess the hydrobionts and current recommendations for material processing. This work represents a continuation of our research launched in 2015 in the coastal area of Tyuleniy Island and its inner lagoon. The qualitative, quantitative and seasonal nature of the distribution of zooplankton in the investigated area of the sea in modern conditions was described. Results. It is shown that the open areas of the island represent a rich taxonomic structure and high density, consisting of a mixed freshwater and brackish-water hydrobiont complex. Conclusions. In general, the zooplankton complex of the Tyuleniy Island water area is a fairly stable ecosystem with a well-developed plankton community. However, for a more complete assessment of its state, seasonal dynamics, and potentials of its food supply for the fish population in the water area, long-term comprehensive monitoring studies are needed.